Mutual Validation of Data Sets for Analyzing Tilt Angles in Solar Active Regions - Lang Qin; Jie Jiang; Ruihui Wang (The Astrophysical Journal)
The tilt angle of solar active regions (ARs) is crucial for the Babcock–Leighton-type dynamo models in the buildup of the polar field. However, divergent results regarding properties of tilt angles were reported due to their wide scatter, caused by intrinsic solar mechanisms and measurement errors. Here, we mutually validate the magnetogram-based AR tilt angle data set from Wang, Jiang, and Luo with the Debrecen Photoheliographic Data by identifying common data points where both data sets provide comparable tilt angles for the same AR/sunspot. The mutually validated data sets effectively reduce measurement errors, enabling a more accurate analysis of the intrinsic properties of tilt angles. Our mutually validated data sets reveal that the difference between white-light-based and magnetogram-based tilt angles is not significant. Also, the data sets show that an upward revision of average tilt angle ( $\bar{α }$ ) and a downward revision of the tilt scatter ( σ _α ) compared to previous results are necessary, with typical values of about 7° and 16°, respectively. The σ _α values demonstrate a strong correlation with AR flux and sunspot area, with the dependency functions reevaluated using mutually validated data sets. Furthermore, both $\bar{α }$ and the tilt coefficient for the weak cycle 24 are larger than those for cycle 23. This supports the tilt quenching mechanism, which posits an anticorrelation between the cycle-averaged tilt angle and cycle amplitude. Additionally, tilt angle from the mutually validated data set has a weak nonmonotonic relationship with magnetic flux and does not depend on the maximum magnetic field strength of ARs.